Tratamentos alternativos para a cicatrização de feridas : potencial regenerativo e atividade enzimática da fração soro do látex de Hancornia speciosa Gomes - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
Over the years, man has tried to interfere in the physiological process of skin regeneration, since this process has been increasingly altered due to the occurrence of fibrosis and the development of chronic wounds. The developing of new technologies able to accelerate the wound healing process and reducing possible complications are necessary. Sometimes the standard treatment modalities are not enough to heal chronic wounds, which are wounds of difficult healing and that require complementary therapies. It is important that these therapies are inexpensive and available to everyone. The use of natural resources such as plants represents a promising alternative for wound healing. With the aim of providing an alternative and low-cost treatment for wound care, this work evaluated the regenerative potential of H. speciosa latex serum using mice and the chorioallantoic membrane of the chicken embryo as a model. Considering the different alternatives for the treatment of wounds available on the market nowadays, we performed a systematic review to evaluate the main types of products and / or therapies that have been proposed for the treatment of diabetic wounds. After that, we evaluated the regenerative potential of H. speciosa latex serum (incorporated into a standardized gel-cream) in full-thickness wounds of rats. Another objective was to evaluate the role of proteins in the angiogenic activity of H. speciosa latex serum using the CAM model. As a result, it was observed that among the wide variety of technologies that have been used for the management and treatment of wounds, those that stood out for their widespread use and relevant regenerative effect were negative pressure wound therapy and therapies with cells and with bioengineering tissues. In addition, the biological tests carried out showed that the serum fraction of the latex of Hancornia speciosa has regenerative potential in rat wounds, in addition to having low protein content and relevant enzymatic activity. Therefore, the latex of H. speciosa has been shown to be able to interfere in the healing process and to assist in the healing phases. This plant has therapeutic potential to be investigated and possibly used in the future as an inducer of tissue regeneration.
Alternative treatments for wound healing: regenerative potential and enzymatic activity of the serum fraction from Hancornia speciosa Gomes latex
Keywords: Biomaterial; Lactíferas; Lesão tecidual; Mangabeira; Regeneração cutânea; Biomaterial; Mangabeira; Tissue damage; Lactiferous; Skin regeneration; CIENCIAS BIOLOGICAS